Newly Reported Colonies of Ivory Gulls on Southeastern Ellesmere Island - France, R.L.; Sharp, M. (ARCTIC, 1992)
Seven colonies of Ivory gulls comprising 330 adults were discovered on nunataks emerging from the Manson Icefield of southeastern Ellesmere Island. This brings to total 33 the number of active colonies that have been located in North America over the 14 years since the first was discovered.Key words: Ivory gull colonies, Manson Icefield, Ellesmere Island Mots clés: colonies de mouettes blanches, glacier Manson, île d’Ellesmere